Core-shell structured pt-w based catalysts, methods of making and using the same, and methods of selective hydrogenolysis
Patent Information
- Application Number
- CN202510557527.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2026-10-30
AI Technical Summary
[0008]本发明的目的是为了克服现有技术存在的催化剂的反应活性和水热稳定性较差,目标产物选择性较低,贵金属容易流失的问题,提供一种核壳结构Pt-W基催化剂及其制备方法与应用、选择性氢解反应的方法,该催化剂在改善催化剂活性和目标产物选择性高的前提下,稳定性大幅提升
[0021](1)本发明提供的Pt-W基催化剂通过氧化铝纳米薄膜将Pt贵金属活性组分固定在内核表面,在氧化铝纳米薄膜外负载W氧化物,提高催化剂的催化活性的同时,维持催化剂的水热稳定性;
Smart Images

Figure CN122999266A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst material synthesis, specifically to a core-shell structured Pt-W-based catalyst, its preparation method and application, and a method for selective hydrogenolysis reaction. Background Technology
[0002] 1,3-Propanediol, 1,5-Pentanediol, and 1,6-Hexanediol are important chemical intermediates and key monomers for the synthesis of high-end polyesters. Currently, the industrial production of 1,3-propanediol, 1,5-pentanediol, and 1,6-hexanediol mainly uses petroleum refining, which has problems such as high energy consumption, non-renewable raw materials, difficulty in separating reaction products, and environmental pollution.
[0003] A method for the catalytic conversion of glycerol to 1,3-propanediol was reported in the literature (Chinese Journal of Catalysis, 2020, 41, 1261-1267), and the stability of the Pt-W-based catalyst was investigated after 700 hours of continuous operation in a fixed-bed reactor. After 700 hours of reaction, the glycerol conversion decreased from the initial 58% to 25%, and the loss of the precious metal Pt content reached 8.7 wt%.
[0004] The literature (ACS Catal. 2018, 8, 1427-1439) reports a method for selective hydrogenolysis of tetrahydrofurandiethanol to 1,6-hexanediol using a Pt-W-based catalyst, with a 1,6-hexanediol yield of up to 70%. However, the Pt content is as high as 10%, and no reports on catalyst stability have been found.
[0005] The literature (Catalysis Today, 2018, 303, 207-212) reports a method for selective hydrogenolysis of tetrahydrofurfural to 1,5-pentanediol using a Pt-W-based catalyst. The maximum yield of 1,5-pentanediol is 43%, with a Pt content of 3%. No reports on catalyst stability have been found.
[0006] CN112169795A discloses an activation method for a polyol hydrogenolysis catalyst, which uses a mixture of hydrogen and nitrogen as raw material to reduce the catalyst in situ, thereby hydrogenolyzing glycerol to produce 1,3-propanediol and improving the conversion reduction rate of glycerol and the yield of 1,3-propanediol. However, the catalyst can only carry out catalytic reactions for 80 hours, and its long-term stability is poor.
[0007] Therefore, in the conversion of bio-based platform molecules such as glycerol, tetrahydrofurfuryl alcohol, and tetrahydrofurandimethyl alcohol into high-value-added terminal hydroxyl diols, catalysts that can be industrialized and meet the requirements of long-term use are needed. Summary of the Invention
[0008] The purpose of this invention is to overcome the problems of poor catalyst reactivity and hydrothermal stability, low target product selectivity, and easy loss of precious metals in existing technologies. This invention provides a core-shell structured Pt-W-based catalyst, its preparation method and application, and a method for selective hydrogenolysis reaction. This catalyst has significantly improved stability while improving catalyst activity and target product selectivity.
[0009] To achieve the above objectives, the first aspect of the present invention provides a core-shell structured Pt-W-based catalyst, wherein the catalyst has a core-shell structure, comprising a core, a first shell layer, a second shell layer, and an outermost shell layer;
[0010] The core of the catalyst includes heat-resistant inorganic oxides and / or molecular sieves, the first shell layer includes Pt nanoparticles, the second shell layer includes alumina nanofilms, and the outermost shell layer includes W oxides.
[0011] The thickness of the alumina nanofilm is 1-20 nm.
[0012] A second aspect of the present invention provides a method for preparing a core-shell structured Pt-W-based catalyst, wherein the method includes the following steps:
[0013] (1) Pt nanoparticles were loaded onto a core support to obtain the first preproduct;
[0014] (2) Alumina nanofilm was deposited on the surface of the first preproduct by thermal atomic layer deposition to obtain the second preproduct;
[0015] (3) W oxide was loaded onto the surface of the second preproduct and subjected to heat treatment to obtain a core-shell structured Pt-W-based catalyst.
[0016] A third aspect of the present invention provides a catalyst prepared by the method described in the second aspect.
[0017] The fourth aspect of the present invention provides the application of the catalyst described in the first or third aspect in a hydrogenolysis reaction.
[0018] A fifth aspect of the present invention provides a method for selective hydrogenolysis, wherein the method comprises: selectively hydrogenolyzing the reactants in the presence of the catalyst described in the first or third aspect.
[0019] Preferably, the reactants are selected from at least one of glycerol, tetrahydrofurfuryl alcohol, and tetrahydrofurandiethanol.
[0020] The beneficial effects achieved through the above technical solution are as follows:
[0021] (1) The Pt-W-based catalyst provided by the present invention fixes the Pt noble metal active component on the core surface through an alumina nanofilm and loads W oxide on the outside of the alumina nanofilm, thereby improving the catalytic activity of the catalyst while maintaining the hydrothermal stability of the catalyst.
[0022] (2) In this invention, preferably, the preparation method of the catalyst is controllable. When the above catalyst is used for selective hydrogenolysis reaction, it is applied to the synthesis of 1,3-propanediol, 1,5-pentanediol and 1,6-hexanediol from glycerol, tetrahydrofurfuryl alcohol and tetrahydrofurandiethanol. The target product selectivity is high and the stability of the catalyst during long-term operation can be significantly improved. Attached Figure Description
[0023] Figure 1 This is a transmission electron microscope image of the first preproduct of Example 1 without deposited alumina;
[0024] Figure 2 This is a transmission electron microscope (TEM) image of the second pre-product of the deposited alumina thin film in Example 1. Detailed Implementation
[0025] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0026] The first aspect of the present invention provides a core-shell structured Pt-W-based catalyst, wherein the catalyst has a core-shell structure, comprising a core, a first shell layer, a second shell layer, and an outermost shell layer;
[0027] The core of the catalyst includes heat-resistant inorganic oxides and / or molecular sieves, the first shell layer includes Pt nanoparticles, the second shell layer includes alumina nanofilms, and the outermost shell layer includes W oxides.
[0028] The thickness of the alumina nanofilm is 1-20 nm.
[0029] The catalyst provided by this invention has a core-shell structure. The Pt-W-based catalyst fixes the Pt noble metal active component on the core surface through an alumina nanofilm and loads W oxide on the outside of the alumina nanofilm, thereby improving the catalytic activity of the catalyst while maintaining the hydrothermal stability of the catalyst.
[0030] According to the present invention, the type and source of the heat-resistant inorganic oxide are not particularly limited; it can be commercially available or prepared using existing methods, and can be a conventional heat-resistant inorganic oxide in the art, serving as a core carrier. Preferably, the heat-resistant inorganic oxide is selected from at least one of alumina, zirconium oxide, titanium dioxide, and silicon dioxide.
[0031] According to the present invention, the type and source of the molecular sieve are not particularly limited, and it can be commercially available or prepared using existing methods. Preferably, the molecular sieve is selected from at least one of Beta molecular sieve, ZSM-5 molecular sieve, HY molecular sieve, and USY molecular sieve, and more preferably Beta molecular sieve and / or USY molecular sieve. In the present invention, the silicon-aluminum molar ratio (SiO2 / Al2O3) of the molecular sieve is not particularly limited, but is preferably 5-200, and more preferably 10-100.
[0032] According to the present invention, preferably, the average particle size of the kernel is 0.05-10 μm, more preferably 0.1-2 μm. In the present invention, the average particle size of the kernel refers to the average particle size of the kernel particles, which can be a single particle or a particle aggregate formed by the aggregation of several small particles.
[0033] In this invention, the average particle size of the kernel is measured using scanning electron microscopy (SEM). The average value is obtained by randomly measuring the size of 100 kernel particles using NanoMeasurer software. During the measurement process, the average particle size has the conventional interpretation in the art, referring to the particle size; for spherical particles, it refers to the diameter of the sphere; for irregular particles, it refers to the maximum straight-line distance within the particle.
[0034] According to a preferred embodiment of the present invention, the core is selected from at least one of silica, Beta molecular sieve and USY molecular sieve.
[0035] According to the present invention, preferably, the average particle size of the Pt nanoparticles is 0.5-6 nm, for example, 0.5 nm, 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 6 nm, or any range between the two, preferably 2-4 nm. In the present invention, the average particle size of the Pt nanoparticles is measured by transmission electron microscopy (TEM), and the average value is taken from the particle size of 100 randomly measured Pt nanoparticles in the TEM image.
[0036] In this invention, the average particle size of the Pt nanoparticles meets the above-mentioned range limit, the Pt nanoparticles have better loading stability, can be uniformly dispersed on the core surface, and improve the catalytic activity of the catalyst.
[0037] According to the present invention, preferably, the mass percentage of Pt nanoparticles, based on the total weight of the catalyst, is 0.3-4 wt%, for example, 0.3 wt%, 0.5 wt%, 0.8 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, or any range between the two, preferably 0.8-3 wt%, more preferably 0.8-1.8 wt%. In the present invention, the mass percentage of Pt nanoparticles is obtained by ICP testing.
[0038] According to the present invention, preferably, the thickness of the alumina nanofilm is 1-20nm, for example 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 12nm, 14nm, 15nm, 16nm, 18nm, 20nm, or any range between the two, preferably 5-10nm.
[0039] In this invention, the thickness of the alumina nanofilm is precisely controllable, and its distribution on the catalyst surface is uniform. On the one hand, it can confine the Pt nanoparticles in the inner layer, improving stability; on the other hand, its uniform and controllable thickness can effectively disperse the W oxide in the outer layer, improving the selectivity and activity of the catalyst. If the alumina nanofilm is too thin, the confinement effect on the Pt nanoparticles is poor; if the alumina nanofilm is too thick, the catalyst activity decreases.
[0040] In this invention, the thickness of the alumina nanofilm is obtained by transmission electron microscopy (TEM), and the average value of the thickness of the alumina nanofilm at 30 randomly measured locations in the TEM image is taken.
[0041] According to the present invention, preferably, the content of W oxide in the outermost shell layer is 0.3-10% by weight, for example, 0.3% by weight, 0.5% by weight, 1% by weight, 2% by weight, 3% by weight, 4% by weight, 5% by weight, 6% by weight, 7% by weight, 8% by weight, 9% by weight, or 10% by weight, or any range between the two, preferably 3-8% by weight. In the present invention, the mass percentage content of W oxide is obtained by ICP method.
[0042] In this invention, the outermost shell of the catalyst includes W oxide, and W active sites are uniformly dispersed on the outer surface of the catalyst, which can enhance the contact probability and mass transfer effect between the raw material molecules and the W active sites, thereby improving the catalytic activity.
[0043] A second aspect of the present invention provides a method for preparing a core-shell structured Pt-W-based catalyst, wherein the method includes the following steps:
[0044] (1) Pt nanoparticles were loaded onto a core support to obtain the first preproduct;
[0045] (2) Alumina nanofilm was deposited on the surface of the first preproduct by thermal atomic layer deposition to obtain the second preproduct;
[0046] (3) W oxide was loaded onto the surface of the second preproduct and subjected to heat treatment to obtain a core-shell structured Pt-W-based catalyst.
[0047] In this invention, preferably, the preparation method of the catalyst is simple to operate and the conditions are controllable. The obtained core-shell structure Pt-W-based catalyst has high catalytic activity and high hydrothermal stability, which can meet the activity and stability requirements of the catalyst for long-term operation.
[0048] According to the present invention, preferably, in step (1), the method of loading Pt nanoparticles onto the core carrier includes the following steps:
[0049] (A) A mixture containing a platinum source, a surfactant and a solvent is heated under reflux to obtain a colloidal solution of Pt nanoparticles;
[0050] (B) The core carrier was added to the colloidal solution of Pt nanoparticles, and after mixing, solid-liquid separation was performed to obtain the first preproduct.
[0051] According to the present invention, the type of platinum source is not particularly limited and can be any conventional platinum-containing compound that can provide Pt in the art. Preferably, the platinum source is selected from at least one of chloroplatinic acid, platinum nitrate imine, and potassium chloroplatinate.
[0052] According to the present invention, preferably, the amount of platinum source added, based on elemental Pt, is 0.3-4% by weight of the total weight of the catalyst, preferably 0.8-3% by weight, and more preferably 0.8-1.8% by weight.
[0053] According to the present invention, preferably, the amount of platinum source added is based on elemental Pt, and the weight ratio of platinum source: surfactant: solvent in step (A) is (1-5):(5-50):(500-10000), preferably (2-4):(10-30):(1000-5000).
[0054] In this invention, the surfactant is a conventional surfactant in the art, preferably selected from at least one of polyvinylpyrrolidone (PVP), copolyvinylpyrrolidone (PVP / VA), and polyvinyl alcohol (PVA).
[0055] In this invention, the type of solvent is not particularly limited. Preferably, the solvent is selected from at least one of methanol aqueous solution, ethanol aqueous solution and propanol aqueous solution. More preferably, the solvent is ethanol aqueous solution and / or propanol aqueous solution, and the volume ratio of ethanol to water and the volume ratio of propanol to water are each independently 1-8:1.
[0056] In this invention, aqueous solutions of ethanol and propanol are used as solvents, resulting in smaller and more uniformly loaded Pt nanoparticles.
[0057] In this invention, the method of obtaining the mixture is not particularly limited. According to a specific embodiment of the invention, a platinum source, a surfactant, and a solvent are mixed and stirred at room temperature to obtain a mixture. The stirring rate and stirring time are not particularly limited, and those skilled in the art can make adaptive adjustments.
[0058] According to the present invention, preferably, the conditions for heating reflux include: under a protective atmosphere, a heating temperature of 60-180°C, preferably 80-160°C, and a heating time of 0.5-6 hours, preferably 1-5 hours.
[0059] In this invention, the type of protective atmosphere is not particularly limited, but is preferably selected from at least one of argon, nitrogen and helium.
[0060] According to the present invention, preferably, the core carrier comprises heat-resistant inorganic oxides and / or molecular sieves.
[0061] According to the present invention, preferably, the heat-resistant inorganic oxide is selected from at least one of alumina, zirconium oxide, titanium dioxide and silicon dioxide.
[0062] According to the present invention, preferably, the molecular sieve is selected from at least one of Beta molecular sieve, ZSM-5 molecular sieve, HY molecular sieve, and USY molecular sieve, and more preferably from Beta molecular sieve and / or USY molecular sieve. The type and source of the core carrier have been described in the foregoing specification and will not be repeated here.
[0063] In this invention, preferably, step (B) further includes adding a dispersing agent to the core support and the colloidal solution of Pt nanoparticles. The dispersing agent is preferably acetone and / or tetrahydrofuran, and the mixture is then subjected to solid-liquid separation. The volume ratio of the added dispersing agent to the solvent in step (A) is 1-8:1. Adding the dispersing agent can adjust the solubility of Pt nanoparticles in the solution, thereby promoting the uniform loading of Pt nanoparticles on the support.
[0064] In this invention, the method of solid-liquid separation is not particularly limited, but filtration is preferred. After solid-liquid separation, the solid product is dried. The drying conditions are not particularly limited, as long as a dried first pre-product is obtained. Preferably, the drying temperature is 80-120℃ and the drying time is 6-12 hours.
[0065] According to the present invention, preferably, in step (2), the thermal atomic layer deposition process includes:
[0066] (a) The first preproduct is fed into the reaction chamber for atomic layer deposition;
[0067] (b) Introduce aluminum precursor gas into the reaction chamber;
[0068] (c) Introduce a protective gas into the reaction chamber to purge away excess aluminum precursor gas;
[0069] (d) Introduce an oxidant into the reaction chamber;
[0070] (e) A protective gas is introduced into the reaction chamber to purge away excess oxidant;
[0071] Repeating steps (b) to (e) constitutes one cycle, and alumina nanofilms are obtained through cyclic deposition.
[0072] According to the present invention, preferably, the temperature of the reaction chamber of the atomic layer deposition system is 200-400°C, more preferably 220-300°C.
[0073] According to the present invention, preferably, the pulse pressure of the aluminum precursor gas is 15-25 torr, more preferably 16-22 torr; the pulse duration is 2-8s, more preferably 3-6s.
[0074] According to the present invention, preferably, the total amount of the aluminum precursor gas introduced is such that the mass ratio of the generated alumina nanofilm to the first preproduct is 0.03-0.5:1, for example, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.08:1, 0.1:1, 0.12:1, 0.15:1, 0.18:1, 0.2:1, 0.25:1, 0.3:1, 0.4:1, 0.5:1, or any range between the two, preferably 0.06-0.3:1.
[0075] In this invention, the aluminum precursor gas is an aluminum source that is conventionally used in the field as a gas under atomic layer deposition conditions. Preferably, the aluminum precursor gas is selected from at least one of trimethylaluminum, aluminum triacetylacetonate, and aluminum chloride, and is preferably trimethylaluminum.
[0076] In this invention, preferably, the protective atmosphere is selected from at least one of nitrogen, argon and helium.
[0077] According to the present invention, preferably, in step (c), the flow rate of the protective atmosphere purging is 10-25 L / min, more preferably 12-22 L / min; and the time is 3-12 s, more preferably 5-10 s.
[0078] According to the present invention, preferably, the pulse duration of the oxidant is 8-25s, more preferably 10-20s; the pulse pressure is 30-50 torr, more preferably 35-45 torr.
[0079] In this invention, preferably, the oxidant is water vapor and / or oxygen.
[0080] According to the present invention, preferably, the number of cycles is 20-100 times, more preferably 30-80 times.
[0081] According to a preferred embodiment of the present invention, the deposition process includes: introducing aluminum precursor gas into a first preproduct to induce an adsorption reaction; rinsing the remaining aluminum precursor gas with a protective atmosphere; introducing an oxidant; and continuing to react with the aluminum precursor gas adsorbed on the surface of the first preproduct to obtain a second preproduct.
[0082] In this invention, the deposition process further includes rinsing the remaining oxidant with a protective atmosphere after the adsorption reaction is completed.
[0083] In this invention, an alumina nanofilm is deposited on the surface of the first preproduct to fix the Pt nanoparticles supported on the core support, thereby inhibiting the loss and aggregation of the precious metal Pt during the use of the catalyst and improving the long-term stability of the catalyst.
[0084] In this invention, the method of loading W oxide onto the surface of the second preproduct is not particularly limited. According to a preferred embodiment of the invention, an equal-volume impregnation method is used, which includes: mixing the second preproduct with a solution containing a tungsten precursor and then drying it.
[0085] In this invention, the tungsten precursor is a conventional tungsten-containing compound in the art, preferably selected from at least one of ammonium metatungstate, ammonium paratungstate, and sodium tungstate.
[0086] In this invention, the concentration of the solution containing the tungsten precursor is not particularly limited, and those skilled in the art can adjust it adaptively according to the W oxide loading.
[0087] In this invention, the drying conditions are not particularly limited, and those skilled in the art can adapt the drying conditions according to the drying situation. Preferably, the drying temperature is 80-120℃ and the drying time is 6-12 hours.
[0088] According to the present invention, preferably, the heat treatment conditions include: a heat treatment temperature of 100-800℃, preferably 500-600℃; and a heat treatment time of 1-10h, preferably 2-6h.
[0089] According to the present invention, preferably, the weight ratio of the W oxide to the second preproduct is 0.003-0.11:1, more preferably 0.03-0.087:1. The amount of tungsten precursor added is sufficient to ensure that the weight ratio of the W oxide to the second preproduct meets the above range.
[0090] A third aspect of the present invention provides a catalyst prepared by the method described in the second aspect.
[0091] The fourth aspect of the present invention provides the application of the catalyst described in the first or third aspect in a hydrogenolysis reaction.
[0092] In this invention, the above-mentioned catalyst, when applied to hydrogenolysis, can significantly reduce the loss of precious metal Pt, slow down the rate of catalyst activity reduction, improve the long-term operational stability of the catalyst, and reduce the cost required for hydrogenolysis, making it suitable for industrial applications of hydrogenolysis.
[0093] According to the present invention, preferably, the reaction raw materials are selected from at least one of glycerol, tetrahydrofurfuryl alcohol and tetrahydrofurandiethanol.
[0094] In this invention, the above-mentioned catalyst is used to selectively hydrogenolyze 1,3-propanediol, 1,5-pentanediol and 1,6-hexanediol. The reaction conditions are easy to control, the catalyst has high activity, the feed conversion rate and the target product selectivity are high. After long-term operation, the loss rate of precious metal Pt in the catalyst is low, and the feed conversion rate and the target product selectivity are maintained at a high level.
[0095] A fifth aspect of the present invention provides a method for selective hydrogenolysis, wherein the method comprises: selectively hydrogenolyzing the reactants in the presence of the catalyst described in the first or third aspect.
[0096] Preferably, the reactants are selected from at least one of glycerol, tetrahydrofurfuryl alcohol, and tetrahydrofurandiethanol.
[0097] According to the present invention, preferably, the reaction conditions for the selective hydrogenolysis reaction include: a reaction temperature of 120-180°C, preferably 140-170°C; and a hydrogen pressure of 1-8 MPa, preferably 3-6 MPa.
[0098] According to the present invention, the apparatus for the reaction is not particularly limited; preferably, the reaction is carried out in a fixed-bed reactor with a liquid hourly space velocity of 0.05-5 h⁻¹. -1 Preferably 0.1-3h -1 .
[0099] According to a preferred embodiment of the present invention, the aqueous solution of the reactants is contacted with a catalyst to carry out a selective hydrogenolysis reaction.
[0100] In this invention, preferably, the concentration of the aqueous solution of the reaction raw materials is 10-95% by weight, more preferably 20-60% by weight.
[0101] In this invention, the liquid phase refers to the aqueous solution of the reaction raw materials.
[0102] The present invention will be described in detail below through examples and comparative examples. Unless otherwise specified, the reagents and materials used in the following examples and comparative examples are commercially available, and the room temperature is 25°C.
[0103] Polyvinylpyrrolidone is Aladdin's K88-96 (average molecular weight is 1,300,000);
[0104] The Beta molecular sieve is NKF-6 from Nankai Catalyst Plant.
[0105] Example 1
[0106] Catalyst A1 was prepared using the following steps:
[0107] (1-A) Measure 250 mL of water and 250 mL of ethanol as a mixed solvent and place them in a 1 L round-bottom flask. Add chloroplatinic acid solution and PVP (polyvinylpyrrolidone) to the flask, stir for 5 min, then heat to 100 °C and reflux for 3 h under an argon atmosphere to obtain a Pt nanoparticle colloidal solution. The weight ratio of platinum source, polyvinylpyrrolidone and mixed solvent, calculated as platinum element, is 1:20:3000.
[0108] (1-B) Add 10g of Beta molecular sieve core support to the above Pt nanoparticle colloidal solution, add acetone, stir for half an hour, filter and separate, and dry at 100℃ for 8 hours to obtain the first preproduct.
[0109] The Beta molecular sieve core carrier has an average particle size of 0.1 μm, and the volume of acetone is 4 times that of the Pt nanoparticle colloidal solution.
[0110] (2-a) The first preproduct is fed into the atomic layer deposition reaction chamber, where the temperature is controlled at 220°C and the pressure is controlled at 0.32 torr;
[0111] (2-b) Trimethylaluminum is introduced into the reaction chamber with a pulse duration of 3s and a pulse pressure of 18 torr;
[0112] (2-c) Nitrogen gas is introduced into the reaction chamber to purge away excess trimethylaluminum. The nitrogen flow rate is 15 L / min and the pulse time is 6 s.
[0113] (2-d) Water vapor is introduced into the reaction chamber. The pulse duration is 12s and the pulse pressure is 34 torr.
[0114] (2-e) Nitrogen gas is introduced into the reaction chamber to purge excess water vapor. The nitrogen flow rate is 15 L / min and the time is 6 s.
[0115] Repeat steps (2-b) to (2-e) to form a cycle. Repeat this cycle 50 times to obtain the second preproduct. The mass ratio of alumina to the first preproduct is 0.2:1.
[0116] (3) Dissolve a certain amount of ammonium metatungstate in 12 mL of water, add 10 g of the second preproduct to the above solution and impregnate it in equal volume, stir for 10 minutes, dry at 100 °C for 8 h, and heat treat at 550 °C for 3 h to obtain the final catalyst A1.
[0117] In this case, the weight ratio of tungsten trioxide to the second preproduct is 0.05:1, based on the mass of W oxide.
[0118] Figure 1 This is a transmission electron microscope (TEM) image of the first preproduct of Example 1 without deposited alumina. Figure 1 As can be seen, the Pt nanoparticles are uniformly loaded on the core carrier; Figure 2 This is a transmission electron microscope (TEM) image of the second preproduct of the deposited alumina thin film in Example 1. Figure 2 It can be seen that the Beta core has lattice stripes, while the alumina film does not. The presence or absence of lattice stripes can be used to determine whether it is Beta or alumina, and then the thickness of the alumina film can be measured.
[0119] Example 2
[0120] The core-shell structured Pt-W-based catalyst A2 was prepared using the method of Example 1. The difference is that in step (2), the atomic deposition cycle was repeated 120 times, and the mass ratio of alumina to the first preproduct was 0.4:1. The catalyst parameters and reaction results are listed in Table 1.
[0121] Example 3
[0122] Catalyst A3 was prepared using the following steps:
[0123] (1-A) Measure 150 mL of water and 350 mL of ethanol as a mixed solvent and place them in a 1 L round-bottom flask. Add platinum nitrate solution and PVA (polyvinyl alcohol) to the flask, stir for 5 min, then heat to 100 °C and reflux for 2.5 h under an argon atmosphere to obtain a Pt nanoparticle colloidal solution. The weight ratio of platinum source, polyvinylpyrrolidone and mixed solvent, calculated as platinum element, is 1:20:2000.
[0124] (1-B) Add 20g of silica support (average particle size of 0.25μm) to the above Pt nanoparticle colloidal solution, add acetone (the volume of acetone is 4 times that of the Pt nanoparticle colloidal solution), stir for half an hour, filter and separate, and dry at 130℃ for 2 hours to obtain the first preproduct.
[0125] (2-a) The first preproduct is fed into the atomic layer deposition reaction chamber, where the temperature is controlled at 240°C and the pressure is controlled at 0.35 torr.
[0126] (2-b) Trimethylaluminum is introduced into the reaction chamber with a pulse duration of 4s and a pulse pressure of 20 torr;
[0127] (2-c) Introduce nitrogen into the reaction chamber to purge away excess trimethylaluminum. The nitrogen flow rate is 18 L / min and the time is 5 s.
[0128] (2-d) Water vapor is introduced into the reaction chamber. The pulse duration is 10s and the pulse pressure is 38 torr.
[0129] (2-e) Nitrogen gas is introduced into the reaction chamber to purge excess water vapor. The nitrogen flow rate is 18 L / min and the time is 5 s.
[0130] Repeat steps (2-b) to (2-e) to form a cycle. Repeat this cycle 60 times to obtain the second preproduct. The mass ratio of alumina to the first preproduct is 0.26:1.
[0131] (3) Dissolve a certain amount of ammonium paratungstate in 12 mL of water, add 10 g of the second preproduct to the above solution, stir for 10 minutes, dry at 100 °C for 8 h, and heat treat at 500 °C for 4 h to obtain the final catalyst A3.
[0132] In this case, the mass ratio of tungsten trioxide to the second preproduct is 0.06:1, based on the mass of W oxide.
[0133] Example 4
[0134] The core-shell structured Pt-W-based catalyst A4 was prepared using the method of Example 1, except that the amount of tungsten precursor added in step (3) was changed. The mass ratio of tungsten trioxide to the second preproduct was 0.02:1 based on the mass of W oxide. Other conditions were the same as in Example 1, and the final catalyst A4 was obtained.
[0135] Example 5
[0136] The core-shell structured Pt-W-based catalyst A5 was prepared using the method of Example 1, except that in step (1-A), 250 mL of water and 250 mL of methanol were measured as a mixed solvent instead of water and ethanol. Other conditions were the same as in Example 1, and the final catalyst A5 was obtained.
[0137] Comparative Example 1
[0138] The core-shell structured Pt-W-based catalyst D1 was prepared using the method of Example 1, except that the entire process of step (2) was not performed, that is, the synthesized catalyst did not have a second layer of alumina nanofilm. The catalyst parameters are listed in Table 1.
[0139] Comparative Example 2
[0140] A certain amount of ammonium metatungstate was dissolved in 12 mL of water. 10 g of silica support was added to the solution for equal-volume impregnation. The mixture was stirred for 10 minutes, dried at 100 °C for 8 hours, and then heat-treated at 550 °C for 3 hours to obtain the first preproduct. Next, the first preproduct was loaded with Pt components using an equal-volume impregnation method and calcined at 400 °C for 3 hours to obtain the final catalyst D2. The loading amounts of Pt and W were the same as in Example 1.
[0141] Catalyst parameters for the examples and comparative examples are shown in Table 1.
[0142] Table 1
[0143] Catalyst number Second shell thickness / nm W oxide content / weight % Example 1 A1 6 4.98 Example 2 A2 12 4.99 Example 3 A3 8 4.98 Example 4 A4 6 2.01 Example 5 A5 6 4.98 Comparative Example 1 D1 0 4.99 Comparative Example 2 D2 0 4.99
[0144] Test Case 1-9, Comparative Test Case 1-4
[0145] Weigh 1g of the catalyst obtained above and place it in a fixed bed. Under the conditions of reaction temperature of 160℃ and hydrogen pressure of 5MPa, the reaction is carried out at a rate of 1h. -1 A 50 wt% aqueous solution of the reactants was introduced at a space velocity of [value missing]. Liquid samples were collected from the outlet at the initial stage (first 4 hours) and at 360 hours for gas chromatography analysis. Catalyst parameters and reaction results are listed in Tables 2 and 3.
[0146] Table 2
[0147]
[0148] Table 3
[0149]
[0150] The results in Tables 1, 2, and 3 show that the catalyst prepared according to this invention exhibits higher hydrothermal stability compared to the catalyst synthesized in Comparative Example 1 in the selective hydrogenolysis of secondary hydroxyl groups in glycerol, tetrahydrofurfuryl alcohol, and tetrahydrofurandimethylethanol to synthesize 1,3-propanediol, 1,5-pentanediol, and 1,6-hexanediol. It significantly inhibits the loss and aggregation of the noble metal Pt, improving catalyst stability and laying the foundation for promoting the industrial application of bio-based high-end glycol polyester monomers. Insufficient W oxide loading or excessively thick alumina nanofilm will lead to a decrease in catalyst activity.
[0151] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A core-shell structured Pt-W-based catalyst, characterized in that, The catalyst has a core-shell structure, including a core, a first shell, a second shell, and an outermost shell. The core of the catalyst includes heat-resistant inorganic oxides and / or molecular sieves, the first shell layer includes Pt nanoparticles, the second shell layer includes alumina nanofilms, and the outermost shell layer includes W oxides. The thickness of the alumina nanofilm is 1-20 nm.
2. The catalyst according to claim 1, wherein, The heat-resistant inorganic oxide is selected from at least one of alumina, zirconium oxide, titanium dioxide, and silicon dioxide; Preferably, the molecular sieve is selected from at least one of Beta molecular sieve, ZSM-5 molecular sieve, HY molecular sieve and USY molecular sieve, and more preferably Beta molecular sieve and / or USY molecular sieve. Preferably, the average particle size of the kernel is 0.05-10 μm, and more preferably 0.1-2 μm.
3. The catalyst according to claim 1 or 2, wherein, The average particle size of the Pt nanoparticles is 0.5-6 nm, preferably 2-4 nm; Preferably, the Pt nanoparticles comprise 0.3-4% by weight, more preferably 0.8-3% by weight, based on the total weight of the catalyst.
4. The catalyst according to any one of claims 1-3, wherein, The thickness of the alumina nanofilm is 5-10 nm; Preferably, the content of W oxide in the outermost shell layer is 0.3-10% by weight, preferably 3-8% by weight, based on the total weight of the catalyst.
5. A method for preparing a core-shell structured Pt-W-based catalyst, characterized in that, The method includes the following steps: (1) Pt nanoparticles were loaded onto a core support to obtain the first preproduct; (2) Alumina nanofilm was deposited on the surface of the first preproduct by thermal atomic layer deposition to obtain the second preproduct; (3) After loading W oxide onto the surface of the second preproduct and performing heat treatment, a core-shell structured Pt-W-based catalyst is obtained.
6. The preparation method according to claim 5, wherein, In step (1), the method of loading Pt nanoparticles onto the core support includes the following steps: (A) A mixture containing a platinum source, a surfactant and a solvent is heated under reflux to obtain a colloidal solution of Pt nanoparticles; (B) The core carrier was added to the colloidal solution of Pt nanoparticles, and after mixing, solid-liquid separation was performed to obtain the first preproduct; Preferably, the core carrier comprises heat-resistant inorganic oxides and / or molecular sieves; Preferably, the heat-resistant inorganic oxide is selected from at least one of alumina, zirconium oxide, titanium dioxide, and silicon dioxide; Preferably, the molecular sieve is selected from at least one of Beta molecular sieve, ZSM-5 molecular sieve, HY molecular sieve and USY molecular sieve, and more preferably Beta molecular sieve and / or USY molecular sieve.
7. The preparation method according to claim 6, wherein, The platinum source is selected from at least one of chloroplatinic acid, platinum nitrate imine, and potassium chloroplatinate. Preferably, the amount of platinum source added, based on elemental Pt, is 0.3-4% by weight of the total weight of the catalyst, preferably 0.8-3% by weight. Preferably, the amount of platinum source added is based on elemental Pt, and the weight ratio of platinum source: surfactant: solvent in step (A) is (1-5):(5-50):(1000-5000), preferably 1:(10-30):(1500-3000). Preferably, the heating reflux conditions include: under a protective atmosphere, a heating temperature of 60-180℃, preferably 80-160℃, and a heating time of 0.5-6h, preferably 1-5h.
8. The preparation method according to claim 5, wherein, In step (2), the thermal atomic layer deposition process includes: (a) The first preproduct is fed into the reaction chamber for atomic layer deposition; (b) Introduce aluminum precursor gas into the reaction chamber; (c) Introduce a protective gas into the reaction chamber to purge away excess aluminum precursor gas; (d) Introduce an oxidant into the reaction chamber; (e) A protective gas is introduced into the reaction chamber to purge away excess oxidant; Repeating steps (b) to (e) constitutes one cycle, and alumina nanofilms are obtained through cyclic deposition.
9. The preparation method according to claim 8, wherein, The reaction chamber temperature of the atomic layer deposition system is 200-400℃, preferably 220-300℃; Preferably, the pulse pressure of the aluminum precursor gas is 15-25 torr, more preferably 16-22 torr; the pulse duration is 2-8s, more preferably 3-6s. Preferably, the pulse duration of the oxidant is 8-25 s, more preferably 10-20 s; the pulse pressure is 30-50 torr, more preferably 35-45 torr; Preferably, the oxidant is water vapor and / or oxygen; Preferably, the flow rate of the protective atmosphere purging is 10-25 L / min, more preferably 12-22 L / min; the time is 3-12 s, more preferably 5-10 s; Preferably, the number of cycles is 20-100 times, and more preferably 30-80 times.
10. The preparation method according to claim 5, wherein, The heat treatment conditions include: a heat treatment temperature of 100-800℃, preferably 500-600℃; and a heat treatment time of 1-10h, preferably 2-6h. Preferably, the weight ratio of the W oxide to the second preproduct is 0.003-0.11:1, more preferably 0.03-0.087:
1.
11. The catalyst prepared by the method according to any one of claims 5-10.
12. The use of the catalyst according to any one of claims 1-4 and 11 in hydrogenolysis reactions.
13. A method for selective hydrogenolysis, characterized in that, The method includes: selectively hydrogenating the reactants in the presence of the catalyst described in any one of claims 1-4 and 11; Preferably, the reactants are selected from at least one of glycerol, tetrahydrofurfuryl alcohol, and tetrahydrofurandiethanol. Preferably, the reaction conditions for the selective hydrogenolysis reaction include: a reaction temperature of 120-180℃, more preferably 140-170℃; and a hydrogen pressure of 1-8 MPa, more preferably 3-6 MPa. Preferably, the reaction is carried out in a fixed-bed reactor with a liquid hourly space velocity (LHSV) of 0.05-5 h⁻¹. -1 Preferably 0.1-3h -1 .
Citation Information
Patent Citations
Optimized activation method of polyol hydrogenolysis catalyst
CN112169795A
